Development of Sequence-Tagged Site Marker Set for Identification of J, JS, and St Sub-genomes of Thinopyrum intermedium in Wheat Background - Qiao, Linyi; Liu, Shujuan; Li, Jianbo; Li, Shijiao; Yu, Zhihui; Liu, Cheng; Li, Xin; Liu, Jing; Ren, Yongkang; Zhang, Peng; Zhang, Xiaojun; Yang, Zujun; et al. (Frontiers in Plant Science, 2021)
Thinopyrum intermedium (2n=6x=42, JJJsJsStSt) is one of the important resources for wheat improvement. So far, a few Th. intermedium (Thi)-specific molecular markers have been reported, but the number is far from enough to meet the need of identifying alien fragments in wheat-Th. intermedium hybrids. In this study, 5,877,409 contigs were assembled using the Th. intermedium genotyping-by-sequencing (GBS) data. We obtained 5,452 non-redundant contigs containing mapped Thi-GBS markers with less than 20% similarity to the wheat genome and developed 2,019 sequence-tagged site (STS) molecular markers. Among the markers designed, 745 Thi-specific markers with amplification products in Th. intermedium but not in eight wheat landraces were further selected. The distribution of these markers in different homologous groups of Th. intermedium varied from 47 (7/12/28 on 6J/6St/6Js) to 183 (54/62/67 on 7J/7St/7Js). Furthermore, the effectiveness of these Thi-specific markers was verified using wheat-Th. intermedium partial amphidiploids, addition lines, substitution lines and translocation lines. Markers developed in this study will provide a convenient, rapid, reliable and economical method for identifying Th. intermedium chromosomes in wheat. In addition, this set of Thi-specific markers can also be used to estimate genetic and physical locations of Th. intermedium chromatin in the introgression lines, thus providing valuable information for follow-up studies such as alien gene mining.